RETRACTED: Computer modelling of socio-economic dynamics: A framework for evaluating the demographic development - Kupriyanova Marina; Evdokimova Elena; Bannikov Sergey (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001